(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Being touted as the biggest scandal in terms of value, the Parmalat scandal offers a good opportunity to investigate and analyze the role of corporate governance in the failure of corporations particularly in the United States, Europe, as well as in emerging economies. This paper examines Parmalats history and describes the circumstances that led to the massive accounting fraud and collapse of Europes and indeed one of the worlds leading dairy producers. This paper highlights and points out how weak and ineffective corporate governance structure and process heavily contributed to other problems within Parmalat and eventually led to its demise in the fall of 2003. This paper incorporates various studies conducted in the past on corporate governance and corporate failure. Organizations with strong and effective corporate governance structure and processes demonstrate better performance in all areas than those with weak corporate governance processes.